Evaluation of Risk Management Implementation in Import Duty Tariff Determination Based on Ministerial Regulation - Yanuar, Yos Ricki; Chaerul D. Djakman (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The potential for shortfalls in state revenue, coupled with recurring findings related to the Internal Control System, highlights the presence of unmanaged or ineffectively managed risks. This study aims to evaluate the extent to which risk management implementation at the XYZ Government Office aligns with the provisions outlined in the relevant Ministerial Regulation on risk management. Employing a qualitative case study approach, data were collected through method triangulation—comprising documentation and interviews—and source triangulation involving key informants. The findings indicate that risk management is largely perceived as a procedural formality. As a result, core processes such as risk identification, analysis, evaluation, and mitigation are not executed effectively. This undermines the ability to uncover root causes and leads to a consistent underestimation of actual risk exposure.